Study of the Principle of Ultra Petitum Partium in Civil Cases - Lubis, Fauziah; Nasution, Khairiah; Br. Limbong, Dhiya Ramadhani; Hasibuan, Suci Khairani; Lubis, Putri Aggraini; Haiqal, Muhammad Fikri (Ilmu Hukum Prima (IHP), 2025)
This study aims to examine the limitations of judges' authority in issuing civil case decisions based on the principle of ultra petitum partium. The main problem in this study is that there are still judges' decisions that exceed the petitum, thus raising questions about the limits of judicial authority and the consistency of the application of the principles of procedural law. The principle of ultra petitum partium is one of the fundamental principles in civil procedural law which emphasizes that judges may not issue decisions beyond the demands of the disputing parties. This principle functions to maintain objectivity, neutrality, and balance in the role of judges in resolving cases. This study uses a normative legal method with a statutory approach and analysis of a number of court decisions directly related to the application of this principle. The results of the study show that the application of this principle is important to prevent abuse of authority by judges. However, in certain conditions such as cases concerning the public interest, public order, or protection of vulnerable parties, judges are allowed to issue decisions exceeding the petitum. Therefore, the application of this principle must be carried out proportionally and contextually in order to create a fair and just trial.